Advancements in Sericulture: Innovations and Sustainability in Silk - Attri, Kapil; G S, Sujatha; Jekinakatti, Basanagouda; D, Thrilekha; Devi, Dharanikota Lalithambica; Garai, Ishita; Satapathy, Satya Narayan; Tripathy, Abhisek (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Sericulture, the cultivation of silkworms for silk production, has a long history intertwined with cultural heritage and economic significance. This paper explores the historical evolution, contemporary relevance, and recent advancements in sericulture, with a focus on sustainability and technological innovation. The traditional process of silk production, including the life cycle of silkworms and mulberry cultivation, has been enhanced through modern techniques. Recent technological innovations, including genetic engineering of silkworms, automated rearing systems, and improved mulberry cultivation methods, have significantly increased productivity and silk quality. Furthermore, advancements in biotechnology have introduced sustainable practices such as the use of artificial diets and controlled environments for silkworms, reducing the industry's environmental footprint. Sustainable practices, such as organic sericulture, integrated pest management, and eco-friendly dyeing techniques, are transforming the industry towards environmental stewardship. By adopting these advancements, sericulture is poised to continue its legacy of luxury and economic importance, while embracing a more sustainable and prosperous future.